Paper Preparation Guidelines for IRPhE'2014 Proceedings (Armenian National Academy of Sciences)
Include in this space an abstract reporting the major aims and results of your contribution (A minimum of 8 and a maximum of 10 lines). Use Times New Roman font, 10 pt, simple interline, left and right justified. For the title, author's names and affiliations, the margins are 2.5 cm left and 2.5 cm right, and for the abstract use 3.5 cm left and right.
Keywords: Physics; Conferences